Women's Experiences of Decisions-Making on Embryo Cryopreservation and Conceptualization of Their Frozen Embryo - Elif Özçetin; Esra Şahiner; İlkay Boz (Atatürk University, 2024)
Objective: The aim of this research is to clarify the experiences of women in deciding on the Embryo Cryopreservation (EC) procedure and the meanings they attribute to their frozen embryos.Methods: This study employed a descriptive phenomenological design and a thematic analysis approach rooted in Husserl's philosophical perspective. Random sampling techniques and maximum diversity sampling methods were both utilized, with data collected between April and October 2021 via semi-structured, in-depth interviews.Results: Following the analysis of the interviews, five themes and 10 sub-themes emerged. The themes were the following: ''Decision-making pathways in embryo cryopreservation'', ''Motivators in the embryo cryopreservation process'', ''Reflections on embryo cryopreservation'', ''Conceptualization of the frozen embryo'', and ''Expectations from the healthcare system''.Conclusion: In this investigation, it was discovered that women expressed discomfort with embryo cryopreservation when decisions were solely made by doctors without adequate information about the process. Furthermore, it was found that women tend to hold a more positive perception of embryos as the quality of frozen embryos improves.